Consolidation and virtualization are in the modern networks of DPCS - Гамаюн, В. П.; Боровик, В. Н.; Боровик, Д. В. (Problems of Informatization and Management, 2010)
The considered methods of consolidation and virtualization are in architecture of construction of high-performance computer networks of DPCS. During an analysis perspective directions are educed on the increase of their productivity